SUSTAINABLE DEVELOPMENT OR CAPITAL SUSTAINABILITY? REFLECTIONS ON GREEN CAPITALISM - de Freitas Ferreira Junior, Euthímio (Revista Gênero e Interdisciplinaridade, 2023)
This work aims to demonstrate how capitalism acts in favor of its commercial interests and how it appropriates nature to make profits. One of the most recent strategies adopted by capitalism is the use of a sustainable development discourse, however, in practice, capital continues to degrade and deforest nature. This discourse, used by capitalism, attributes a more human character to the degradation and inappropriate use of natural resources. Consequently, many people adopt this false sustainability discourse and practices. However, it is possible to observe that the problem is not limited to the discourse, but to the capitalist system as a whole.